Oxidative degradation of chitosan by Fe-MCM-41 heterogeneous Fenton-like system - Zhang Zhang; Wuheng Dong; Yongchun Huang (Scientific Reports, 2024)
Abstract We herein disclosed an efficient multiphase Fenton-like catalytic system for oxidative degradation of chitosan. By utilizing Fe-MCM-41, featured with regular mesoporous structure and high specific surface area, the activation efficiency of H2O2 was significantly enhanced and the chitosan degradation efficiency proved by 28.1% higher than the conventional system using H2O2 alone. Under optimized conditions (5 g/L chitosan, 0.5 g/L Fe-MCM-41, 0.16 mol/L CH3COOH, 0.86 mol/L H2O2, 50 °C, 140 min), the viscosity reduction rate of chitosan reached an impressive 98.2%. Among the catalysts tested, Fe-MCM-41 with a loading factor of x = 0.12 demonstrated optimal degradation performance. After four recycles, the degradation efficiency maintained > 93.6%, demonstrating its excellent stability and recyclability for potential industrial applications. Kinetic studies provided further elucidation of the reaction mechanism, which indicated that the degradation process of chitosan followed a first-order kinetic model, with an apparent activation energy (Ea) of 48.91 kJ/mol. This novel and efficient strategy for chitosan degradation, addressed the challenges of catalyst recovery and secondary pollution typically associated with traditional Fenton systems, and posed broad application potential for polysaccharide material processing.